Genetic Polymorphisms in TLR2, TLR4, IL-10, and IL-17A: Possible Effect on Pertussis Acellular Vaccine Response - Anabe, Denise (My University, 2023)
Pertussis, a highly infectious respiratory disease caused by Bordetella pertussis, is still endemic despite primary vaccination rates of 81% in 2021. Variability toward vaccination response due to genetic polymorphisms has been noted in other vaccines, as well as in the acellular pertussis vaccine, wherein up to 10% of individuals fail to mount sufficient antibody responses. We hypothesize that this variability may be attributed to polymorphisms in TLR2, TLR4, IL-17A, and IL-10. The pathogen recognition receptors TLR2 and TLR4 recognize B. pertussis and its antigens and initiate immune responses. The pro-inflammatory cytokine IL-17A stimulates the recruitment of neutrophils to protect against infection, whereas the anti-inflammatory IL-10 regulates immune responses and prevents hyperinflammatory-related pathologies. A total of 124 subjects from the Booster Pertussis Vaccine Study were genotyped using PCR-based technologies and a repeated measures mixed model was used to analyze the effect of polymorphisms on vaccine responses. We showed that these polymorphisms may affect vaccine responses in an age-dependent manner. Children and adolescents who carry variant type TLR4, and wild type TLR2 and IL-17A had higher antibody responses, but this was reversed in older adults. Moreover, subjects with low- or intermediate-producing IL-10 genotypes and haplotypes were associated with higher antibody responses. However, further replication and functional validation is required in another Finnish cohort with a larger sample size to confirm results. Findings in this study may lead to considerations of these polymorphisms when designing future vaccine policies to protect those with polymorphisms associated with low pertussis vaccine responses.
Keywords: Pertussis, Vaccines, Genetic Polymorphisms